Do Intellectually Gifted Children Have Better Planning Skills? - Li Cheng; Xiaohe Xie; Shiting Yang; Linjie Xiao; Xiaoyu Chen; Yun Nan; Dong Qi; Jagannath P. Das; George K. Georgiou (Journal of Intelligence)
The present study aimed to examine whether intellectually gifted children had better planning skills than their chronological-age controls and what processing skills may explain these differences. A total of 35 intellectually gifted Chinese children (25 boys and 10 girls; Mage = 12.77 years) and 39 chronological-age controls (27 boys and 12 girls; Mage = 12.89 years) participated in this study. They were assessed on three measures of operational planning (Planned Codes, Planned Connections, and Planned Search), on a measure of action planning (Crack the Code), and on measures of processing speed, working memory, and attention. Results of analysis of variance (ANOVA) showed first that the two groups differed in Crack the Code (accuracy and first move time) and in Planned Connections. Whereas processing speed explained the group differences in Planned Connections, none of the processing skills were able to eliminate the group differences in Crack the Code. Taken together, these findings suggest that gifted children have better action planning, which allows them to perform better than controls in tasks that require complex problem solving and evaluation of different scenarios and solutions.